Comment une ville traditionnelle turque a-t-elle réussi à attirer les citadins en opérant une transformation historique et naturelle pour répondre aux attentes urbaines ? - Janna Leann Rose (Développement Durable et Territoires)
The processes through which urban centers and rural peripheries influence each other reach beyond landscapes and town borders into something deeper and more culturally substantial. Over the past decade, a rural village in Turkey has been re-constructing itself to represent a nostalgic historical era that is part of the local natural landscape that draws in urban tourists from the national capital. The process through which the villagers re-constructed the past and commoditized parts of it is an interesting case in that the villagers dispelled any fears of backwardness in their historical situated-ness via their selective process. This allayed fears and legitimized the trip for urban city-dwellers. While the tensions between the village and the city are not essentially ethnic but socio-economic and class-based in Turkey, the village, as it now stands, allows a space and a place for both urban and rural Turks to play with and re-negotiate their collective historical consciousness. Perhaps this play and interaction leads to the valuation of traditional ways in a positive instead of negative light.cultural transformation, rural tourism, natural landscapes, identity reconfiguration, turkish villages